Turning Points in Middle Eastern History - Gearon, Eamonn; Kanopy (Firm). ([San Francisco, California, USA] : Kanopy Streaming, 2017)
Much media coverage, however, is incomplete at best, failing to take account of either the complexities or the historical background of this pivotal region. For most of us, the real story of the Middle East remains untold. What made this crucial geopolitical area what it is today? What forces and factors underlie what we read in the news, and what drives the current challenges the Middle East both faces and poses? In coming to terms with the present and future of the Middle East, an understanding of its history is not only highly valuable, but essential.
collection
Originally produced by The Great Courses in 2016.
In English
Keywords: Educational films; Middle East; Middle Eastern Studies